2008
DOI: 10.1007/s11262-008-0295-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of synonymous codon usage in the UL24 gene of duck enteritis virus

Abstract: The analysis on codon usage bias of UL24 gene of duck enteritis virus (DEV) may improve our understanding of the evolution and pathogenesis of DEV and provide a basis for understanding the relevant mechanism for biased usage of synonymous codons and for selecting appropriate expression systems to improve the expression of target genes. The codon usage bias of UL24 genes of DEV and 27 reference herpesviruses were analyzed. The results showed that codon of UL24 gene of DEV was strong bias toward the synonymous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 50 publications
2
26
2
Order By: Relevance
“…A previous study has shown that the codon usage pattern of the DPV dUTPase gene is phylogenetically conserved and similar to that of the dUTPase genes of the avian ␣ -herpesvirus [39] . Furthermore, analysis of codon usage bias in the UL24 gene of DPV also indicates that the synonymous codon usage pattern of the UL24 gene in DPV is similar to other avian ␣ -herpesviruses and the UL24 gene's function also contributes to the codon usage [38] . So, we can infer from these studies that the codon usage pattern of DPV is similar to that of avian ␣ -herpesvirus; however, the conclusive evidence may require further analysis of other DPV genes, such as viral genes for maintenance or replication.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A previous study has shown that the codon usage pattern of the DPV dUTPase gene is phylogenetically conserved and similar to that of the dUTPase genes of the avian ␣ -herpesvirus [39] . Furthermore, analysis of codon usage bias in the UL24 gene of DPV also indicates that the synonymous codon usage pattern of the UL24 gene in DPV is similar to other avian ␣ -herpesviruses and the UL24 gene's function also contributes to the codon usage [38] . So, we can infer from these studies that the codon usage pattern of DPV is similar to that of avian ␣ -herpesvirus; however, the conclusive evidence may require further analysis of other DPV genes, such as viral genes for maintenance or replication.…”
Section: Discussionmentioning
confidence: 84%
“…However, intraspecific variation does not fit neutral mutational models as well, suggesting that deviations in the effectiveness of selection among loci is likely to be an important force for shaping patterns of intragenomic codon usage variation across all domains of life [33] . Recently, analyses of the patterns of codon usage bias of herpesviruses are primarily focused on the pseudorabies virus [20] , herpes simplex virus type 1 (HSV-1) [36] , Epstein-Barr virus [37] , UL24 gene [38] and dUTPase gene [39] of the duck plague virus (DPV).…”
mentioning
confidence: 99%
“…There are 64 codons to code 20 amino acids and the start and stop signals. Most amino acids were coded by more than one codon (synonymous codons) [2], but the synonymous codon usage are not used equally both within and between genomes [3][4]. Previous research have been showed that codon usage bias may be very complicated and associated with various biological factors, such as gene expression level [5], gene length [6], gene translation initiation signal [7], protein amino acid composition [8], protein structure [9], tRNA abundance [10,11], mutation frequency and patterns [8,12], GC composition [13,14], and environmental factors [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, analyses of the patterns of codon usage bias of herpesviruses are primarily focused on the pseudorabies virus (PRV) [21], herpes simplex virus type 1 (HSV-1) [22], Epstein-Barr virus [23]. However, except for UL24, UL26.5, UL35, gE, dUTPase, the codon usage bias in DPV genome was known little [2,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…With many similarities and a few differences, accumulating evidence indicates that the UL35 protein and its homologues of Alphaherpesvirus , Betaherpesvirus and Gammaherpesvirus may play similar roles in viral assembly and maturation. To date, the majority of reported DPV sequences are limited to single open reading frames, which include UL5-UL6 [16,18,19] , UL22-UL24 [20][21][22] , UL25-UL30 [23] , UL31-UL35 [24][25][26][27] , UL44 [28,29] , UL50-UL51 [30][31][32] , US3-US5 [33,34] , US8 [35] , US2 and US10 [36] . However, no reports have been published concerning the characterization of transcription, expression, intracellular localization and the dependence of DPV VP26 on viral DNA synthesis.…”
mentioning
confidence: 99%